Cognitive Conflict Strategy Assisted by PhET Simulation to Remediate Student's Misconceptions on Wave Material - Diajeng Iffatul Hasanah; Wasis Wasis (Asatiza: Jurnal Pendidikan, 2021)
In this era, a misconception is one of the biggest challenges in education. Misconception is an understanding of a concept but incompatible with a scientific concept. This research aimed to describe the profile of students' misconceptions and to analyze the decrease of student misconceptions using a cognitive conflict strategy assisted by PhET Simulation. The kind of research is the pre-experimental category with the design of One Group Pre-Test and Post-Test. The sample of this research is a student of XII IPA 2 SMA Negeri 1 Bangkalan. The results of the pre-test showed that the average percentage of students who experience misconception is 53.53%. Based on the pre-test analysis, it was found 20 forms of conceptions that students had regarding the traveling wave material. After being given treatment using a cognitive conflict strategy assisted by PhET simulation, the post-test results of students who experienced misconceptions became 7.65%. There is a decrease in the average percentage of students who experience misconceptions in the pre-test and post-test results. It shows that the cognitive conflict strategy assigned by PhET simulation is effective in remediating the misconceptions of students on wave material.